Memahami Manajemen Islam Melalui Pendekatan Tafsir Metodologis: Memahami Manajemen Islam Melalui Pendekatan Tafsir Metodologis - Fathul Aminudin Aziz (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2018)
Qur'an is the answer and the solution of any problems existing in this Earth, including the answers and solutions toward understanding the field of management. Understanding Islamic managements can be conducted by implementing various approaches of interpretation (tafsir). One of the approaches is the methodological interpretation approach. This approach emphasizes on understanding â€œlafdziâ€ and â€œmaknawiâ€. Therefore, it is so rare or even there is no formula or method of management science has been found yet. This research elaborates new insight about understanding Islam through methodological interpretation approach by explaining some aspects that consist of: (a) communication, (b) minimal parameter, (c) leadership, (d) progressive, and (e) problem solving.